Administration of microencapsulated Enterococcus faecium ABRIINW.N7 with fructo-oligosaccharides and fenugreek on the mortality of tilapia challenged with Streptococcus agalactiae - Nami, Yousef; Kahieshesfandiari, Mahdi; Lornezhad, Gilda; Kiani, Amir; Elieh-Ali-Komi, Daniel; Jafari, Mahdieh; Jaymand, Mehdi; Haghshenas, Babak (Frontiers in Veterinary Science, 2022)
We investigated the probiotic potential of a microencapsulated E. faecium ABRIINW.N7 for control of Streptococcus agalactiae infection in hybrid (Oreochromis niloticus × Oreochromis mossambicus) red tilapia. A two-phase experiment approach was completed in which E. faecium bacteria were propagated, from which a culture was isolated, identified using molecular techniques, and microencapsulated to produce a stable commercial fructooligosaccharide (FOS) and fenugreek (Fk) product of optimal concentration. The FOS and Fk products were assessed in a 12-week in vivo challenge study, in which red hybrid tilapia were allocated to one of five treatments: No Streptococcus agalactiae (Sa) challenge (G01) (CON); Sa challenge only (G02) (CON+); Sa challenge in a free cell (Free Cell) G03; Sa challenge with 2% (w/v) Alginate (G04); Microencapsulated FOS and Fk (G05-G011). In vitro results showed high encapsulation efficiency and acceptable viability of probiotic bacteria within the simulated fish digestive system and high stability of viable cells in all gel formulations. In vivo challenges demonstrated that the G05-G011 FOS and Fk products could be used to control S. agalactiae infection in tilapia fish and represented a novel investigation using microencapsulation E. faecium as a probiotic diet for tilapia fish to control S. agalactiae infection and to lower fish mortality. It is recommended that local herbal gums such as Persian gum (PG) and Fk in combination with alginate (ALG) can be used as a suitable scaffold and an ideal matrix for the encapsulation of probiotics. These herbal gums as prebiotics are capable of promoting the growth of probiotic cells in the food environment and digestive tract.